Carl Stamitz (1745–1801) - Kaiser, Fritz (2023)
Carl Stamitz (1745-1801), Johann Stamitz's eldest son, is well known for his works, as his compositions can be found on numerous recordings and concert programmes in today's music scene. Musicologists though do not pay the same attention to this composer, who came from the ranks of the court musicians of the Electoral Palatinate. The dissertation by Friedrich Carl Kaiser (1931-2008), submitted in 1962, is still the only monograph that systematically deals with his life and his orchestral music, which was a major part of his creative work. It is a standard work that rightly appears in every bibliography on the subject. Up to now it has only been possible to view the compulsory typescript copies of the dissertation, which are distributed among a few libraries and which differ in detail from one another. The reason for this is the somewhat unusual genesis of the text, as Kaiser repeatedly made changes and additions to his Stamitz monograph over a long period of time. The present edition, which also includes Kaiser's personal copy from his estate, now provides musicology researchers with a reliable edition of this fundamental text.